Character Education in Preventing the Danger of Radicalism and Terrorism in PAI Learning at School - Hamid, Abdul; Setyawati, Priyatna; Arsy, Risma Fadila (Jurnal Multidisiplin Madani, 2024)
Purpose of this research is how to plan, implement and impact the development of character education values. This research uses descriptive-qualitative research method. While the data collection used is observation, interviews, and documentation. To analyze the data using descriptive-qualitative analysis technique, namely describing existing data to describe reality in accordance with the actual phenomenon. The instruments used were interviews with researchers focusing on research subjects, namely: Principal, Deputy Head of Curriculum, PAI teachers and students representing SMAN 3 Palu. The results of this study are planning aspects; First, the syllabus used by PAI teachers has shown the development of character education values ​​in PAI learning. Second, the lesson plans are adapted by making certain additions, including: 1) adding achievement indicators related to character achievement, 2) adding learning activities related to character development, 3) adding assessment techniques that measure character development. The implementation aspect is the discovery of specific character values ​​that can be used as references in preventing the dangers of radicalism and terrorism in PAI learning, namely: religious, discipline, tolerance, national spirit, independence, care for the environment, responsibility, curiosity, respect for achievement, and social care. Aspects of the impact, are 1) The impact of material development, students can: a) accept the concepts or knowledge being taught, b) respond, c) respect all differences, d) regulate themselves in attitude, 2) Impact on the development of the school environment